A guide to the natural history of the Cedarburg Bog: Part 1 - (:unkn) unknown (My University, 1985)
The boardwalk that extends to the center of the Cedarburg Bog is the UWM Field Station's most heavily used teaching facility. Research is also conducted in the Bog, which holds an understandable fascination for researchers and students of natural history because of its size, complexity, diversity and geographical isolation from similar communities. Because of the increasing research and teaching use of the Bog, it has become essential that some of what is known about the natural history of the Bog be assembled and summarized in an easily accessible introduction and guide. The guide contains too much material to fit into one issue of the Field Station Bulletin. The first issue contains a narrative on each of the vegetation zones through which the boardwalk passes. The second issue has the selected species lists, annotated with natural history notes, which are also arranged by vegetation zones along the boardwalk. The second issue also contains vertebrate and vascular plant species lists for the Cedarburg Bog. An index to both volumes and the literature cited for both volumes are contained in Part I. As research on the Bog continues, I plan to revise this guide periodically to incorporate additional information. The Field Station would appreciate suggestions regarding ways that future editions of this guide might be improved.
Keywords: Cedarburg Bog; natural history; guidebook